Micro-CT Characterization of Wellbore Cement Degradation in SO42-–Bearing Brine under Geological CO2 Storage Environment - Manguang Gan; Liwei Zhang; Xiuxiu Miao; Yan Wang; Xiaojuan Fu; Mingxing Bai; Xiaochun Li (Geofluids)
In order to explore the process of acid- and CO2-induced degradation of wellbore cement and the development of pre-existing leakage channels in wellbore cement under sulfate-rich geological CO2 storage conditions, wellbore cement samples were immersed in SO42--bearing brine solution for 7 days, and the samples after reacting with the low and circumneutral pH solutions were scanned by a micro-CT scanner. HCl+Na2SO4 solution was used to simulate the low-pH condition in deep formation waters and the possible existence of high sulfate ion content in deep formation waters. The acidification and carbonation results were compared, and the results given different pH values and different curing conditions were compared as well. The results show that the degradation of cement was related to the pH value of the reaction solution. There was a significant dissolution in the exterior of the cement sample after exposure to the low-pH solution, but the dissolution surrounding a penetrating borehole at the center of the sample (mimicking a leakage pathway within the wellbore cement in geological CO2 storage environment) was limited. Comparison between acidification and carbonation results in this study shows formation of a thick carbonate layer due to cement carbonation, and this layer was not observed in the acidification result. As for different curing conditions of cement samples, no significant difference in cement alteration depth was observed for the acidification case. For the carbonation case, precipitations in the borehole occurred in the cement sample cured at ambient pressure, while the cement sample cured at high pressure did not produce any precipitation in the borehole. This study provides valuable information on how low pH-induced corrosion and HCO3--induced cement carbonation contribute to structure evolution of wellbore cement in SO42--bearing brine under geological CO2 storage environment.